2016
DOI: 10.1139/cjpp-2015-0303
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac phenylethanolamine N-methyltransferase: localization and regulation of gene expression in the spontaneously hypertensive rat

Abstract: https://mc06.manuscriptcentral.com/cjpp-pubs ABSTRACTPhenylethanolamine N-methyltransferase (PNMT) is the terminal enzyme in the catecholamine biosynthetic pathway responsible for adrenaline biosynthesis. Adrenaline is involved in the sympathetic control of blood pressure; it augments cardiac function by increasing stroke volume and cardiac output. Genetic mapping studies have linked the PNMT gene to hypertension. This study examined the expression of cardiac PNMT and changes in its transcriptional regulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
(109 reference statements)
0
5
0
1
Order By: Relevance
“…2,3 Though the role of hPNMT in the human central nervous system (CNS) has yet to be fully elucidated, epinephrine has been associated with a number of CNS processes such as cardiovascular homeostasis, adrenergic receptor activation, learning and memory, and regulation of the circadian cycle. 1 In addition, studies suggest hPNMT may play a role in several human disease states including hypertension, 4 myocardial infarction, 5 Alzheimer's disease, 6 and Parkinson's disease. 7,8 Recently, density functional theory (DFT) 9 and quantum mechanics/molecular mechanics (QM/MM) 10 methods have been used to investigate the hPNMT reaction mechanism.…”
mentioning
confidence: 99%
“…2,3 Though the role of hPNMT in the human central nervous system (CNS) has yet to be fully elucidated, epinephrine has been associated with a number of CNS processes such as cardiovascular homeostasis, adrenergic receptor activation, learning and memory, and regulation of the circadian cycle. 1 In addition, studies suggest hPNMT may play a role in several human disease states including hypertension, 4 myocardial infarction, 5 Alzheimer's disease, 6 and Parkinson's disease. 7,8 Recently, density functional theory (DFT) 9 and quantum mechanics/molecular mechanics (QM/MM) 10 methods have been used to investigate the hPNMT reaction mechanism.…”
mentioning
confidence: 99%
“…Recent evidence supports that overexpression of the PNMT gene in adrenal glands, heart and brainstem of SHRs is caused by altered transcriptional regulation, and contributes to their hypertensive phenotype [11,23,24]. Studies from our lab have also previously demonstrated that the expression of adrenal PNMT is elevated when offspring are exposed to high doses of DEX prenatally, caused by altered transcriptional mechanisms [25].…”
Section: Introductionmentioning
confidence: 86%
“…Доказана связь между низкими показателями Другие проблемы эндокринологии массы тела при рождении и программированием развития гипертонии с нарушениями развития почек и регуляции ренин-ангиотензин-альдостероновой системы [16], изменением структуры и функции сосудов [17], а также изменением активности гипоталамогипофизарно-надпочечниковой [18] и симпатоадреналовой систем [19,20]. Результаты недавних исследований демонстрируют, что сверхэкспрессия гена фенилэтаноламин-N-метилтрансферазы (PNMT) в надпочечниках, сердце и стволе мозга вызывается изменением регуляции транскрипции и вносит вклад в их гипертензивный фенотип [21]. Ранее были опубликованы данные, свидетельствующие о том, что экспрессия надпочечникового PNMT повышается, когда потомство подвергается пренатальному воздействию высоких доз, что вызвано измененными механизмами транскрипции [22].…”
Section: антенатальная глюкокортикостероидная терапия и риск сердечно...unclassified